2022
DOI: 10.30872/jfor.v24i2.10330
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh literasi keuangan, persepsi kemudahan, manfaat, keamanan dan pengaruh sosial terhadap minat penggunaan fintech

Abstract: AbstrakPenelitian ini bertujuan untuk memberikan hasil pengujian secara empiris faktorfaktor yang mempengaruhi minat generasi milenial di provinsi Bali dalam menggunakan fintech. Teori yang digunakan dalam menganalisis minat penggunaan fintech adalah kombinasi dari teori Technology Accaptence Model (TAM) dan Theory Planned Behavior (TPB) sebagai acuan teroritis penelitian. Jenis penelitian ini adalah kuantitatif dengan probability sampling dan teknik pengambilan sampel simple random sampling menggunakan metode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
1
9
0
8
Order By: Relevance
“…It means that the better financial literacy, the use of QRIS will increase. It is supported by research by Aditya and Mahyuni (2022), who found that financial literacy has a positive effect on the use of QRIS. With sound financial literacy, the use of QRIS will be even better.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…It means that the better financial literacy, the use of QRIS will increase. It is supported by research by Aditya and Mahyuni (2022), who found that financial literacy has a positive effect on the use of QRIS. With sound financial literacy, the use of QRIS will be even better.…”
Section: Introductionmentioning
confidence: 83%
“…Effectively Managing personal finances is essential, covering all levels of society from all walks of life and backgrounds. Research conducted by Rawadiah (2020) and Aditya and Mahyuni (2022) found that financial literacy has a positive effect on the use of QRIS.…”
Section: Discussionmentioning
confidence: 99%
“…One of the strategies that banking companies can apply is paying attention to user convenience that can be easily understood so that customers can easily operate the mobile banking service system (Dirwan, 2018). the results of research conducted by Aditya (2022) show that the influence of perceived ease of use on fintech interest in the millennial generation in Bali province based on testing has a positive and significant relationship. This finding is supported by research conducted which shows that the perception of convenience has a significant positive influence on interest in using the OVO application as an e-money payment tool.…”
Section: Research Hypothesismentioning
confidence: 97%
“…The results of research conducted show that perceptions of security have a positive influence on BNI bank customers' interest in using mobile banking at the BNI Palu Branch. Research results from Aditya (2022) show that the influence of perceived security on interest in using fintech on millennial generalization in Bali province based on testing has a positive and significant relationship. H2: Security has a positive effect on interest in using mobile banking…”
Section: Research Hypothesismentioning
confidence: 99%
“…Perception of security is the extent to which people as users of digital financial services (e-wallets) believe that the technology is safe to use (Khoiriyah, et.al., 2023). The better the security system that the company providing fintech e-wallet services has in protecting the personal information of its users, the higher the number of users using fintech e-wallet services (Aditya & Mahyuni, 2022). Research conducted by Aditya & Mahyuni (2022) shows the results that perceived security has a positive and significant effect on the interest of the millennial generation in Bali province in using fintech, while research conducted by Sukmawati, K & Kowanda, D (2022) & Ananda, P & Nuriyah, A (2023) show results that perceived security does not influence interest in using e-wallet.…”
mentioning
confidence: 99%